2002
DOI: 10.1029/2001jd000982
|View full text |Cite
|
Sign up to set email alerts
|

Background ozone over the United States in summer: Origin, trend, and contribution to pollution episodes

Abstract: [1] Observations indicate that ozone (O 3 ) concentrations in surface air over the United States in summer contain a 20-45 ppbv background contribution, presumably reflecting transport from outside the North American boundary layer. We use a threedimensional global model of tropospheric chemistry driven by assimilated meteorological observations to investigate the origin of this background and to quantify its contribution to total surface O 3 on both average and highly polluted summer days. The model simulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
428
4
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 392 publications
(461 citation statements)
references
References 89 publications
28
428
4
1
Order By: Relevance
“…With increasing expansion of city centers and urban sprawl, unmanaged forest areas will increasingly become recipients of long-range transport of secondary oxidation products of primary urban VOC and NO x emissions. Modeled estimates (Fiore et al, 2002) indicate that anthropogenic emissions in Asia and Europe may increase afternoon O 3 concentrations in surface air over the United States by between 4 and 7 ppb, an enhancement that may be particularly large for O 3 concentrations in the mid range (50e70 ppb). Any rise in background O 3 concentration may, therefore, offset the positive benefits for North American forests accrued from the recent downward trend in peak O 3 concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…With increasing expansion of city centers and urban sprawl, unmanaged forest areas will increasingly become recipients of long-range transport of secondary oxidation products of primary urban VOC and NO x emissions. Modeled estimates (Fiore et al, 2002) indicate that anthropogenic emissions in Asia and Europe may increase afternoon O 3 concentrations in surface air over the United States by between 4 and 7 ppb, an enhancement that may be particularly large for O 3 concentrations in the mid range (50e70 ppb). Any rise in background O 3 concentration may, therefore, offset the positive benefits for North American forests accrued from the recent downward trend in peak O 3 concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…The model includes a detailed description of tropospheric O 3 -NO x -hydrocarbon chemistry. The model has been used in a range of studies, including the analysis of the impact of background O 3 on surface O 3 over North America [e.g., Fiore et al, 2002] and interpretation of in situ aircraft observations from the International Consortium on Atmospheric Transport and Transformation (ICARTT) aircraft campaign over North America [e.g.. Hudman et al, 2007]. We use version v7-02-04 of GEOS-Chem with a horizontal resolution of 2°Â 2.5°and 55 levels in the vertical from the surface to 0.01 hPa, with 5 levels in the PBL.…”
Section: Geos-chem Modelmentioning
confidence: 99%
“…Precise estimates of the tropospheric O 3 budget are desirable in an air quality context as O 3 produced in the free troposphere and the intercontinental transport of O 3 provides a background contribution to O 3 abundances at the surface. It has been estimated [e.g., Fiore et al, 2002;Vingarzan, 2004] that this background source contributes as much as 20-45 ppbv to surface O 3 . Fiore et al [2002] showed that Asian and European anthropogenic emissions increase surface O 3 in North America by 4 -7 ppbv.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is important to determine the spatial distribution of STT and its process for each region, in order to understand the regional characteristics of STT. Many previous studies have focused on STT events in North America using both observations and global models with a horizontal resolution of 50−300 km (Lefohn et al 2001(Lefohn et al , 2011Fiore et al 2002;Langford et al 2009;Bourqui and Trepanier 2010;Lin et al 2012). Some studies have focused on STT events in the Mediterranean, using a global model with a relatively low resolution (~300 km; e.g., Akritidis et al 2016), as well as on events in Europe, using global models with relatively higher resolutions (~100 km), and regional models with a resolution of ~14 km (e.g., Hoffmann et al 2016).…”
Section: Introductionmentioning
confidence: 99%